Holistic Analysis for Fork-Join Distributed Tasks supported by the FTT-SE Protocol - Martínez, Ricardo Garibay (2015)
11th IEEE World Conference on Factory Communication Systems (WFCS 2015). 27 to 29, May, 2015, TII-SS-2: Scheduling and Performance Analysis. Palma de Mallorca, Spain.